Transformation of the “hidden middle” of aquaculture value chains: fish wholesalers in Bangladesh - Ali, Hazrat; Belton, Ben; Haque, Md. Mahfuzul; Hernandez, Ricardo; Khondker, Murshed-E-Jahan; Ignowski, Elizabeth; Reardon, Thomas (WorldFish, 2024)
Wholesalers in food value chains in developing countries are often criticized as exploitative, offering high output-tied credit to farmers and insufficient with high loss and waste. Recent research highlights their importance as the "hidden middle", often overlooked in policy debates due to insufficient survey research (Reardon 2015). Aquaculture has rapidly expanded in Bangladesh in four decades, attributed to aquatic food traders and off-farm businesses. However, little is known about wholesalers’ behavior and organization within the 'hidden middle' of aquatic food value chains, impeding result generalization due to inadequate sampling techniques in previous research. Thus, this study aimed to evaluate structure, technological changes, and wholesalers’ performance, informing policy debates on aquatic food value chains in Bangladesh.